Treatment and survival of locally recurrent rectal cancer: A cross-sectional population study 15 years after the Dutch TME trial. Issue 11 (November 2019) - Detering, Robin; Karthaus, Eleonora G.; Borstlap, Wernard A.A.; Marijnen, Corrie A.M.; van de Velde, Cornelis J.H.; Bemelman, Willem A.; Beets, Geerard L.; Tanis, Pieter J.; Aalbers, Arend G.J.; ,
Abstract: Introduction: Optimized treatment of primary rectal cancer might have influenced treatment characteristics and outcome of locally recurrent rectal cancer (LRRC). Subgroup analysis of the Dutch TME trial showed that preoperative radiotherapy (PRT) for the primary tumour was an independent poor prognostic factor after diagnosis of LRRC. This cross-sectional population study aimed to evaluate treatment and overall survival (OS) of LRRC patients, stratified for prior preoperative radiotherapy (PRT) and intention of treatment of LRRC. Methods: All patients developing LRRC were selected from a collaborative Snapshot study on 2095 surgically treated rectal cancer patients from 71 Dutch hospitals in the year 2011. Cox proportional hazard analysis was performed to determine predictors for OS. Results: A total of 107 LRRC patients (5.1%) were included, of whom 88 (82%) underwent PRT for their primary tumour. LRRC was treated with initial curative intent in 31 patients (29%), with eventual resection in 20 patients (19%). Median OS was 22 and 8 months after curative and palliative intent treatment, respectively (p < 0.001). Initial CRM positivity and palliative intent treatment were associated with worse OS after LRRC, while prior PRT was not. Conclusions: This cross-sectional study revealed that rectal cancer patients, who underwent curative resection in the Netherlands in 2011 and subsequently developed local recurrence, were amenable for again curative intent treatment in 29%, with a corresponding median survival of 22 months. Prior PRT was not significantly associated with survival after diagnosis of LRRC.